Do municipal amalgamations affect interregional migration? - Vífill Karlsson; Grétar Þór Eyþórsson (Veftímaritið Stjórnmál og stjórnsýsla, 2019)
This paper examines the change of interregional migration following municipal amalgamations. Interregional migrations are mostly triggered by differentials in household utilities, local economic conditions, amenities and the like. Thus, it is reasonable to believe that if an amalgamation of municipalities leads to a better service or lower local taxes in a community, it would attract new inhabitants and thus, increase the net-migration - as suggested by Tiebout (1956). A macro panel data set from Iceland was used that represents several essential variables of the housing market for 79 municipalities in Iceland during the period from 1993 to 2006. The results returned mixed effects on net migration. The amalgamations seem to have had both negative and positive effects on net-migration due to the differences in the number of municipalities in each merger and the similarities in the population sizes of the previous municipalities that joined each merger.